The Prognostic Value of Quantitative EEG in Patients Undergoing Mechanical Thrombectomy for Acute Ischemic Stroke. Issue 4 (13th May 2022) - Dickey, Adam S.; Mitsias, Panayiotis D.; Olango, Weredeselam M.; Agan, Matthew C.; Roche, William P.; Thomas, Julien R.; Rodrigues, Gabriel M.; Frankel, Michael R.; Ratcliff, Jonathan J.; Nogueira, Raul G.; Haussen, Diogo C.; Karakis, Ioannis
Abstract : Purpose: Previous work has shown that quantitative EEG measures correlate with the severity of ischemic stroke. This has not been systematically validated in patients with acute ischemic stroke who have undergone mechanical thrombectomy. Methods: Data were collected from 73 patients who underwent mechanical thrombectomy and had a standard head set EEG performed during their hospital admission. For each patient, the global delta-alpha ratio (DAR) and its difference between the two hemispheres were calculated. Associations between the global and interhemispheric DAR difference with the patients' National Institutes of Health Stroke and Modified Rankin Scale scores at discharge and 3 months after thrombectomy were assessed. Results: The interhemispheric DAR difference correlated with the National Institutes of Health Stroke scores at discharge (Spearman R = 0.41, P = 0.0008), National Institutes of Health Stroke scores at 3 months (Spearman R = 0.60, P = 0.02) and Modified Rankin Scale scores at 3 months (Spearman R = 0.27, P = 0.01). In contrast, the global DAR did not correlate significantly with any of these clinical outcomes when evaluated as continuous variables. In a multivariate logistic regression model, both the interhemispheric DAR difference (β = 0.25, P = 0.03) and the infarct volume (β = 0.02, P = 0.03) were independently predictive of good versus poor functional outcome (Modified Rankin Scale score ≤2 vs. >2) at 3 months. Conclusions: The quantitative EEG measure of interhemispheric slow relative to fast frequencies power asymmetry correlated with the discharge and 3-month National Institutes of Health Stroke and Modified Rankin Scale scores and provided added value to infarct volume in predicting functional outcome at 3 months. These data support the prognostic value of quantitative EEG in ischemic stroke patients who have undergone mechanical thrombectomy.